2022
DOI: 10.1002/mds.29229
|View full text |Cite
|
Sign up to set email alerts
|

Brain Atrophy Is Substantially Accelerated in Neurological Wilson's Disease: A Longitudinal Study

Abstract: Background Although brain atrophy is common in neurological Wilson's disease, longitudinal studies are lacking. Objective The objective of this study was to measure longitudinal brain atrophy rate and to relate it to the change in neurological impairment in Wilson's disease. Methods We included patients with brain imaging done at diagnosis and at least 12 months later. The atrophy rate was measured as percentage change in ventricular volume, whereas the change in neurological impairment was scored on the Unifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Our study found that the neurological function score, psychiatric symptom score, and liver function score were low in patients with WD, and the correlation between neurological function score and linear measurement indicators of brain atrophy caused by WD remained to be investigated. Smolinski et al found that patients with neurological manifestations had significantly higher annualized atrophy rates than other patients (Smolinski et al, 2022 ) and that the volume of all major brain structures correlated with functional and neurological impairment in patients with WD (Smolinski et al, 2019 ). In line with previous studies which revealed an association between brain atrophy and cognitive functions (Nagai et al, 2008 ; Liu et al, 2016 ), Kalita et al found that midbrain atrophy was associated with nervous system severity through 3D BRAVO sequence measurements of the midbrain and the pons (Kalita et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found that the neurological function score, psychiatric symptom score, and liver function score were low in patients with WD, and the correlation between neurological function score and linear measurement indicators of brain atrophy caused by WD remained to be investigated. Smolinski et al found that patients with neurological manifestations had significantly higher annualized atrophy rates than other patients (Smolinski et al, 2022 ) and that the volume of all major brain structures correlated with functional and neurological impairment in patients with WD (Smolinski et al, 2019 ). In line with previous studies which revealed an association between brain atrophy and cognitive functions (Nagai et al, 2008 ; Liu et al, 2016 ), Kalita et al found that midbrain atrophy was associated with nervous system severity through 3D BRAVO sequence measurements of the midbrain and the pons (Kalita et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Brain atrophy caused by WD is very common, occurring in 31.6% of patients (Zhong et al, 2019 ; Du and Bydder, 2021 ), and is associated with copper accumulation in the brain (Czlonkowska et al, 2018 ; Dusek et al, 2019 ). One study found a correlation with WD nerve injury by measuring the longitudinal brain atrophy rate (Smolinski et al, 2022 ). Moreover, brain atrophy is a marker of increased risk of death (Lauksio et al, 2021 ; van den Berg, 2022 ), which can be divided into cerebral atrophy, cerebellar atrophy, and brain stem atrophy (Hayashi et al, 2008 ; Christova et al, 2017 ; Gellersen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar result was reported by Dusek et al (2021) that volume instead of susceptibility of the PU was considered related to neurological severity ( Du and Bydder, 2021 ). A recent longitudinal study evaluating annualized brain atrophy found significantly higher brain atrophy rate in neurological WD and its correlation with changes in functional and neurological severity ( Smolinski et al, 2022 ). Thus, the volumetric change and ISOVF may be considered reliable biomarkers for monitoring chronic impairment in WD.…”
Section: Discussionmentioning
confidence: 99%
“…This change in brain volume could be seen as evidence of brain shrinkage, but unfortunately, they didn't do a longitudinal study. However, Smolinski et al's long-term longitudinal study on WD patients ( 3 ) made up for the deficiency in this aspect. They found that the incidence of cerebral atrophy in WD patients with neurological symptoms was significantly higher than that in patients without neurological symptoms, and the rate of cerebral atrophy was related to the degree of neurological function damage in patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SmolinskiLukasz et al ( 2 ) found that the severity of cerebral atrophy is closely related to the neurological impairment of WD patients by measuring the brain volume of WD patients. Later, SmolinskiLukasz et al ( 3 ) conducted a long-term longitudinal study on brain atrophy in WD patients, and found that the incidence of brain atrophy in neurological WD patients was significantly increased, which was related to the progression of neurological impairment. Almost all patients with neurological WD show brain MRI changes ( 4 ).…”
Section: Introductionmentioning
confidence: 99%